Beneficial effects of intermittent fasting: a narrative review - Dae-Kyu Song; Yong-Woon Kim (Journal of Yeungnam Medical Science, 2023)
Caloric restriction is a popular approach to treat obesity and its associated chronic illnesses but is difficult to maintain for a long time. Intermittent fasting is an alternative and easily applicable dietary intervention for caloric restriction. Moreover, intermittent fasting has beneficial effects equivalent to those of caloric restriction in terms of body weight control, improvements in glucose homeostasis and lipid profiles, and anti-inflammatory effects. In this review, the beneficial effects of intermittent fasting are discussed.